h.hofstede (h.hofstede@hogeland.nl)

 
1. t = 3/4π  geeft 
x = cos(3/4π)sin(3/2π) = -1/2√2 -1 = 1/2√2
y = cos(3/4π) = -1/2√2
 
  x ' = -sint sin(2t) + cos(t) 2cos(2t)   dus  x'(3/4π) = -1/2√2 -1 + -1/2√2 2 0 = 1/2√2
y
'= -sint  dus y '(3/4π) = -1/2√2 
 
  ze zijn inderdaad gelijk.
       
2. a y = 0
sin(2t) - sin(t) = 0
sin(2t) = sin(t)
2t = t + k2π  ∨  2t = π - t + k2π
t = 0 + k2π  ∨  3t = π + k2π
t = 0 ∨ t = 2π ∨  t = 1/3π + k2/3π
t = 0 ∨ t = 2πt = 1/3πt = πt = 5/3π
Dat geeft respectievelijk x = 1  ∨ x = 1  ∨  x = -1/2 - 1/2√3  ∨ x = 1 ∨ x = -1/2 + 1/2√3
Voor punt P is x = -1/2 - 1/2√3
       
  b. x = cos(2t) - sin(2t)
x '= -2sin(2t) - 2cos(2t)  dus  x'(0) = -2  en  x '(π) = -2   

y = 
sin(2t) - sin(t)
y' = 2cos(2t) - cos(t)  dus  y '(0) = 1  en  y '(π) = 3
   
   
    α = cos-1(7/√65) = 29,7°
       

h.hofstede (h.hofstede@hogeland.nl)